Group Recommender Systems An Introduction - Felfernig, Alexander; Boratto, Ludovico; Stettinger, Martin; Tkalčič, Marko (SpringerBriefs in Electrical and Computer Engineering,, 2018)
This book presents group recommender systems, which focus on the determination of recommendations for groups of users. The authors summarize different technologies and applications of group recommender systems. They include an in-depth discussion of state-of-the-art algorithms, an overview of industrial applications, an inclusion of the aspects of decision biases in groups, and corresponding de-biasing approaches. The book includes a discussion of basic group recommendation methods, aspects of human decision making in groups, and related applications. A discussion of open research issues is included to inspire new related research. The book serves as a reference for researchers and practitioners working on group recommendation related topics.